Relationships between religious backgrounds, behaviors and emotions of Mu’tamir during Umrah rituals - Sulong, Jasni; Ahmad Hatta, Zulkarnain; Mohd Hashim, Intan Hashimah; Abdul Ghan, Noraida; Abdul Rahman, Shukran (2013)
Umrah is one of the compulsory worship in Islam and the rituals can only be performed at Kaabah and Masjidil al-Haram, Mecca. Muslims from all over the world going to Mecca for this ritual and as a result witnessed crowds of Muslims (mu’tamir). As year by year, the quantity of mu’tamir is accelerating and getting bigger in quantity. This scenario set up a situation of crowds especially during tawaf and saie rituals, which consequently create some negative behaviors and emotions from them. Instead of crowds, negative behaviors and emotions were also influence by the other factors which exists at that time such as, hot weather, limited space, pushing attitudes and scramble for certain place. Therefore, the study was engaged to examine mu’tamir’s behaviors and emotions during the rituals and to show a relationship of both items with religious backgrounds. At this stage, the study was at aim to scrutinize the function of religious backgrounds in preparing a mu’tamir before, during or after performing the rituals. Therefore, a study was carried out by interviewing some respondents from Malaysia and Indonesia. It was found that the religious backgrounds have given a significant influence to the mu’tamir which prepared them mentally and physically to be a good Muslims, as the intention for umrah is for worship. Therefore, they chose to evade every negative behaviors and emotions and focused in achieving the success of worship in preferred form.